2021
DOI: 10.1097/ico.0000000000002829
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 Pandemic on Infectious Keratitis Outcomes: A Retrospective Multicenter Study in Tertiary Eye Hospitals of South India

Abstract: Purpose:The purpose of this study was to report the adverse effects of the COVID-19 pandemic on the clinical outcomes of infectious keratitis in South India.Methods: Two hundred fifty-eight patients presented with infectious keratitis at 6 tertiary care centers when strict travel restrictions were in place from March 24 to May 31, 2020. Case records were collected retrospectively and analyzed for demographics, type of initial treatment, length of delay in presentation, microbiological diagnosis, clinical cours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
1
Order By: Relevance
“…Our study was similar to a similar experience reported from South India on the outcomes of infectious keratitis. Our rate of resolution was lower (35.8%) compared to Christy et al (45.6%), this could be due to the higher incidence of severe keratitis in our study population (48.8% vs. 41.9%) [ 15 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Our study was similar to a similar experience reported from South India on the outcomes of infectious keratitis. Our rate of resolution was lower (35.8%) compared to Christy et al (45.6%), this could be due to the higher incidence of severe keratitis in our study population (48.8% vs. 41.9%) [ 15 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Nearly 23% of patients with emergency corneal problems lost their vision permanently due to a lack of surgical intervention. [ 18 ] Based on our results, a significant portion of patients with infectious keratitis or trauma will need a repeat transplant at some point for optical clarity. Therefore, the use of glycerin-preserved corneas and gamma-irradiated grafts that can be preserved for 2 years at room temperature could be utilized in emergency situations to 1) allow the patient to undergo surgery sooner and 2) save the fresh tissue for optical purposes rather than therapeutic.…”
Section: Discussionmentioning
confidence: 93%
“…Table 5 summarizes various comparative and noncomparative studies on microbiological and demographic profile of corneal ulcers during COVID-19. [ 29 30 31 32 33 ] The current study is the only prospective study on demographic and microbiological profile of corneal ulcers during COVID-19 era.…”
Section: Discussionmentioning
confidence: 99%